Influence of extended light exposure curing times on the degree of conversion of resin-based pit and fissure sealant materials - Nazish Fatima (Elsevier, 2014)
Purpose: The aim of present study was to evaluate extended curing times on the degree of conversion (DC) of filled and unfilled resin-based materials used as pit and fissure sealants. Materials and methods: The materials examined were a flowable composite (Filtek™ Z350 XT Flowable) and a pit and fissure sealant (Clinpro™ Sealant). Thirty disks of each material were prepared. The 30 made of the flowable composite were divided into three groups (n = 10 each) according to the three different curing times studied: 20 s (group 1), 40 s (group 2), and 60 s (group 3). Similarly, the 30 disks made of the pit and fissure sealant were divided into three groups (n = 10 each) according to the three different curing times: 20 s (group 4), 40 s (group 5), and 60 s (group 6). After polymerization, the disks were removed from the mold and stored in dry, lightproof containers in an incubator at 37 °C for 24 h. The DC was obtained using an Avatar 320 FTIR spectrometer. Then the data were analyzed using the Kruskal-Wallis test and the Fisher's least significant difference post hoc test for multiple comparisons (alpha = 0.05). Results: DC values for the flowable composite (Filtek™ Z350 XT) were higher (p = 0.002) than those for the pit and fissure sealant (Clinpro™ Sealant). Group 2 and group 5 showed significantly higher DC values than group 1 and group 4, respectively. There was no difference between groups 2 and 3 or between groups 5 and 6 (p = 2.93). Conclusion: An extended curing time improves the DC to some extent for both materials. Keywords: Degree of conversion, Pit and fissure sealants, Curing time, Spectrometer